A DFT study on the molecular properties of synthetic ester under the electric field - Wang Yachao (De Gruyter, 2021)
Synthetic ester can replace the mineral oil traditionally used in transformers to avoid the environmental problems caused by oil leakage. However, the fast discharge phenomenon in a high electric field in transformers using synthetic ester seems to indicate its insulation property is inferior to that of mineral oil. In this paper, typical molecular models of synthetic ester, including F2, F4, F6, F8, and F10, are constructed. We studied the effect of electric fields on the molecular properties of the five molecules by density functional theory and time-dependent density functional theory. According to the electric field intensity required for discharge initiation and propagation in insulating oil, the electric field intensity applied in this study varied from 108 to 109 V/m. The results showed that the molecular bond lengths are obviously dependent on the electric field. The ionization potential (IP) of the F8 and F10 molecules decreases sharply under electric field intensities of 3.1 × 109 and 4.0 × 109 V/m. It can be inferred that the IP reduction of the long carbon chain molecules, such as F8 and F10, is the reason for the formation of fast discharge in the case of synthesis ester. Calculations for excited states show that the introduction of an electric field makes the electron transition more active. The results obtained by this work improve our understanding of the discharge mechanism in synthetic ester dielectrics and provide theoretical support for improvement in the performance of synthetic ester insulating oil.